2021
DOI: 10.1038/s41598-021-82764-6
|View full text |Cite
|
Sign up to set email alerts
|

Addressing unpredictability may be the key to improving performance with current clinically prescribed myoelectric prostheses

Abstract: The efferent control chain for an upper-limb myoelectric prosthesis can be separated into 3 key areas: signal generation, signal acquisition, and device response. Data were collected from twenty trans-radial myoelectric prosthesis users using their own clinically prescribed devices, to establish the relative impact of these potential control factors on user performance (user functionality and everyday prosthesis usage). By identifying the key factor(s), we can guide future developments to ensure clinical impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Unlike rigid 'tools' that have fixed intrinsic properties, the reliability of prosthesis responsiveness can fluctuate as a result of EMG signal artefact arising from sweating, poor fitting and/or fatigue 58 . Indeed, recent evidence has shown that prosthesis users who experience a greater frequency of undesired activations (hand accidentally opening/closing, no prosthesis response, or incorrect prosthesis response) during a shoulder flexion task are also more likely to exhibit decreased functionality and an increased time watching the prosthesis during a multi-stage functional task 59 . This tentatively suggests that the expectation of an undesired prosthesis response (i.e., users do not trust their device) drives both poor performance and the over-reliance on gaze to visually monitor prosthesis control and safeguard against (the possibility of) task failure.…”
Section: Hand-eye Coordination and The Utility Of Gaze Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike rigid 'tools' that have fixed intrinsic properties, the reliability of prosthesis responsiveness can fluctuate as a result of EMG signal artefact arising from sweating, poor fitting and/or fatigue 58 . Indeed, recent evidence has shown that prosthesis users who experience a greater frequency of undesired activations (hand accidentally opening/closing, no prosthesis response, or incorrect prosthesis response) during a shoulder flexion task are also more likely to exhibit decreased functionality and an increased time watching the prosthesis during a multi-stage functional task 59 . This tentatively suggests that the expectation of an undesired prosthesis response (i.e., users do not trust their device) drives both poor performance and the over-reliance on gaze to visually monitor prosthesis control and safeguard against (the possibility of) task failure.…”
Section: Hand-eye Coordination and The Utility Of Gaze Trainingmentioning
confidence: 99%
“…This tentatively suggests that the expectation of an undesired prosthesis response (i.e., users do not trust their device) drives both poor performance and the over-reliance on gaze to visually monitor prosthesis control and safeguard against (the possibility of) task failure. Addressing the issue of prosthesis unpredictability could therefore be crucial to the development of effective prosthesis visuomotor control and the alleviation of cognitive resources dedicated to continuous prosthesis monitoring 59 .…”
Section: Hand-eye Coordination and The Utility Of Gaze Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Even minor changes to the imaging angle can drastically affect an acquired ultrasound image and cause the classifier to misidentify the user’s intended hand gesture. Unintended hand movements due to misclassification may lead to reduced task completion rates, slower task performance, increased temporal variability, and increased cognitive load ( Chadwell et al, 2021 ). Thus, grasp classification must be sufficiently stable under varying arm positions and loading conditions for the user to consistently achieve their desired hand grasps throughout the reachable workspace.…”
Section: Introductionmentioning
confidence: 99%
“…Even minor changes to the imaging angle can drastically affect an acquired ultrasound image and cause the classi er to misidentify the user's intended hand gesture. Unintended hand movements due to misclassi cation may lead to reduced task completion rates, slower task performance, increased temporal variability, and increased cognitive load (Chadwell et al, 2021). Thus, grasp classi cation must be su ciently stable under varying arm positions and loading conditions for the user to consistently achieve their desired hand grasps throughout the reachable workspace.…”
Section: Introductionmentioning
confidence: 99%